217k views
2 votes
17t + 4t − 5t − 13t = 18

2 Answers

4 votes

Answer:

T=6

Explanation:

Isolate t on one side of the equation.

17+4t-5t-13t=3t (Combine like terms & group like terms )

3t=18

3t/3=18/3 (Divide by 3 from both sides.)

18/3 (Solve.)

18/3=6

t=6

Therefore, the final answer is t=6.

User Jdsurya
by
5.1k points
3 votes

17t + 4t − 5t − 13t = 18

do 17t+4t first

21t-5t-13t

21t-5t and then do -13t

16t-13t= 18

3t= 18

divide both sides by 3 to get t by itself

3t/3= 18/3

cross out 3 and 3, divide by 3 and then becomes 1*1*t= t

t= 18/3

Answer:

t= 6

User Ersen Osman
by
5.4k points